An Investigation of the Prescription Patterns of Chinese Herbal Products for Chronic Glomerulonephritis Patients: A Hospital-Based Cross-Sectional Study. (15th November 2018) - Chen, Wen; Chen, Hsing-Yu; Yang, Yao-Hsu; Yang, Sien-Hung; Yang, Ching-Wei; Wu, You-Hung; Chen, Jiun-Liang
Abstract : Chronic kidney disease (CKD) has a high incidence and prevalence worldwide, and chronic glomerulonephritis (CGN) is one of the main causes of CKD. Therefore, it is important to diagnose and treat CGN early. The purpose of this study is to analyze the prescription patterns and frequencies of Chinese herbal products (CHPs) for CGN by using a hospital-based database from the Chang Gung Memorial Hospital (CGMH), a large, tertiary hospital system in Taiwan, and to evaluate the safety and possible efficacy of CHPs by blood test. The International Classification of Disease Ninth Revision (ICD-9) code 582 was used to identify patients with CGN. From 2004 to 2015, a total of 54726 CHP prescriptions for CGN were provided. Association rule mining was used to analyze the prevalent of CHP combination patterns in treating CGN. Jia-Wei-Xiao-Yao-San (JWXYS) and Gorgon (Euryale feroxSalisb.) were the most frequently prescribed herbal formula (HF) and single herb (SH), respectively. The most frequently prescribed combination of CHPs was that of JWXYS with Bu-Yang-Huan-Wu-Tang (BYHWT) in CGMH. In statistical, the level of eGFR in Stage 3a and 3b group was increasing after treatment in 6 and 12 months and might not cause the renal function to worsen within 12-month treatments. To the best of our knowledge, this is the first pharmacoepidemiological study to review CHP treatments for CGN. However, additional studies and clinical trials are needed to provide data on the safety and efficacy of these CHPs.